PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 2 SUNGAI RAYA - Lestari, Rara (Universitas Tanjungpura, 2018)
This research aimed to investigate how the effect of make a match model on learning achievement of tenth grade students of SMA Negeri 2 Sungai Raya regency. The method used was quasi experimental that comprised two sample classes as control class and experimental class. The sample were selected using purposive sampling. The result showed that: (1) the mean score of students